PENGEMBANGAN BUKU PANDUAN PRAKTIKUM KIMIA HIDROKARBON BERBASIS KETERAMPILAN PROSES SAINS DI SMA - Zulaiha Zulaiha; Hartono Hartono; A. Rachman Ibrahim (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2014)
Development of Cemistry Lab Manual for Hydrocarbons Based Science Process Skills at Senior High School. This research aims to produce a high school chemistry lab manual for hydrocarbons subject with science process skill-based which is valid, practical and has a potential effect. The method used is Development Research with the reference of model ADDIE (Analysis, Design, Development, Implementation, Evaluation) and the formative evaluation of Tessmer, such as Evaluation Expert Review, One-to-One, Small Group, and Field Test. The results show the score of validity is 128 which is included in the category of very valid, the practicality score is 1337 which is included in the category of very practical and the students’ final test results indicate that the manual book has the potential effect of 81,21. These results show that the chemistry lab manual with science process skill-based is valid, practical and has a potential effect.